Assessing the strategic competitiveness of the Malaysian medium density fibreboard industry - Othman, Mohd Shahwahid; Abdul Samad, Abdul Rahim (Institute of Interdisciplinary Business Research, 2010)
Within three decades, the medium density fibreboard (MDF) industry has grown and contributed significantly to the external trade of the wood-based sector of Malaysia. Today the industry is at a cross road. Although, trade is expanding, but initial relative advantages over other competitors have marginally eroded. Over time new critical success factors played important roles as the industry responded to changes in global challenges. New strategies and tactical actions were undertaken. Through an industrial survey using the strength, weakness, opportunity and threat (SWOT) approach, this paper assesses the strategic competitiveness position of the MDF industry in Peninsular Malaysia.